Active and Inclusive Teaching of Literacy and Communication Skills for Enhanced Employment and Sustainable Economic Growth (University of Maribor Press, 2024)
The monograph presents a part of the research work within the project "Active and Inclusive Teaching of Literacy and Communication Skills for Enhanced Employment and Sustainable Economic Growth (In-Comm Guide)," and underscores the significance of communication skills for both business success and personal development. These skills are deemed essential not only in academic achievements but also in the professional realm, with employers actively seeking them in prospective candidates. The monograph emerges as a product of the Erasmus+ initiative – the project was supported by the European Union and overseen by the Slovenian national agency CMEPIUS. Encompassing a consortium of institutions including the University of Maribor, University of Applied Sciences Zwickau, University of Pula, and University of Udine, the project aimed to develop communication skills curricula. This focus sought to bolster students’ readiness for the job market while emphasizing non-verbal communication, sign languages, and linguistic proficiency, particularly in English. Within the monograph, the emphasis on innovative teaching methodologies, intercultural communication, and students’ well-being converge. Moreover, attention is directed toward individuals with hearing impairments and the significance of non-verbal communication.